Ultrahigh-efficiency solar energy harvesting via a non-concentrating evacuated aerogel flat-plate solar collector. (August 2022) - Gao, Datong; Wu, Lijun; Hao, Yong; Pei, Gang
Abstract: Non-concentrating solar collector is extensively used in residential and industrial sectors for low-temperature (<120 °C) applications. The current non-concentrating solar collectors are underperformed in the intermediate temperature range (120–300 °C), which immensely limits their application. In this paper, a structure-optimized evacuated flat plate solar collector with a transparent aerogel layer and back shield plate is proposed to solve the above issue. The experimental test is conducted to validate the numerical model of the evacuated flat plate solar collector and the spectral properties of the transparent aerogel layer. The analysis results manifest that the structure optimized evacuated aerogel flat-plate solar collector possesses ultrahigh thermal efficiency in the low and intermediate temperature range with a relatively thin aerogel layer (5 mm) adopted and it is superior to state-of-the-art work. The thermal efficiency of the evacuated aerogel flat-plate solar collector is 60.47% at an inlet temperature of 155 °C, which is a 20.68% enhancement over that of the prototype collector. This research is fundamental to the future development of non-concentrating solar collectors and instrumental in the decarbonization goal for residential buildings and industrial heating energy supplements. Highlights: An evacuated flat-plate solar collector with radiative shieldings has been proposed. The radiative loss is inhibited with only 5 mm aerogel layer implementation. The thermal efficiency reaches 60.47% at 1 kW/m 2 and temperature of 155 °C. A much broader work temperature range (50–300 °C) is achieved for applications.